2018
DOI: 10.1007/s13312-018-1275-7
|View full text |Cite
|
Sign up to set email alerts
|

Second Dose of Scorpion Antivenom in Children with Indian Red Scorpion (Mesobuthus tamulus) Sting Envenomation

Abstract: Children with severe scorpion sting envenomation with abnormal echocardiography may require a higher dose of scorpion antivenom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In general, the existence of myocardial dysfunction and the severity of the envenomation are well correlated with troponin levels making troponin a good screening tool especially [ 34 , 55 ]. Other studies showed that CK-MB is likely to be elevated in most envenomations (even those without cardiac dysfunction), while NT-proBNP and troponin are more specific markers of cardiac dysfunction [ 55 , 57 , 58 , 106 ]. Khalaf et al [ 52 ] found low sensitivity and specificity for CK-MB [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the existence of myocardial dysfunction and the severity of the envenomation are well correlated with troponin levels making troponin a good screening tool especially [ 34 , 55 ]. Other studies showed that CK-MB is likely to be elevated in most envenomations (even those without cardiac dysfunction), while NT-proBNP and troponin are more specific markers of cardiac dysfunction [ 55 , 57 , 58 , 106 ]. Khalaf et al [ 52 ] found low sensitivity and specificity for CK-MB [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 The two antivenom ampoules administered here are deemed sufficient to treat severe envenomations 29 ; however, lack of additional antivenom doses precluded further immunotherapy, as recommended previously when worsening to higher degrees of envenomation occurs within 6 hours of the first dose. 30 The severity of this case and the local antivenom shortage demand implementation of appropriate health measures, including adequate supplies of specific antivenoms in remote endemic areas of eastern Ecuador and elsewhere in the Amazon Basin, to reduce the time elapsed between sting and antivenom administration for treatment of envenomed children and pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Abimannane et al reported that treatment of children showing autonomic symptoms from Indian red scorpion envenomation that could lead to myocardial infarction required second dose of 30 mg (3 ml) [25]. However, reference was not made to the weight of the children.…”
Section: Treatment Of Scorpion Envenomation Requires Body Weightmentioning
confidence: 99%
“…Therefore, there is need to reassess treatment of Mesobuthus tamulus envenomation in children. The formula developed by Saganuwan [26] [25] indicating that the initial dose of the antivenin should be 30 mg (3 ml) followed by 60 mg (6 ml) of the second dose. The second dose should be 24 mg (2.4 ml).…”
Section: Treatment Of Scorpion Envenomation Requires Body Weightmentioning
confidence: 99%